Enhancing Effects of NMDA-Receptor Blockade on Extinction Learning and Related Brain Activation Are Modulated by BMI - Golisch, Anne; Heba, Stefanie; Glaubitz, Benjamin; Tegenthoff, Martin; Lissek, Silke (Frontiers in Behavioral Neuroscience, 2017)
A distributed network including prefrontal and hippocampal regions is involved in context-related extinction learning as well as in renewal. Renewal describes the recovery of an extinguished response if the context of extinction differs from the context of recall. Animal studies have demonstrated that prefrontal, but not hippocampal N-methyl-D-aspartate receptor (NMDAR) antagonism disrupted extinction learning and processing of task context. However, human studies of NMDAR in extinction learning are lacking, while NMDAR antagonism yielded contradictory results in other learning tasks. This fMRI study investigated the role of NMDAR for human behavioral and brain activation correlates of extinction and renewal. Healthy volunteers received a single dose of the NMDAR antagonist memantine prior to extinction of previously acquired stimulus-outcome associations presented in either identical or novel contexts. We observed better, and partly faster, extinction learning in participants receiving the NMDAR antagonist compared to placebo. However, memantine did not affect renewal. In both extinction and recall, the memantine group showed a deactivation in extinction-related brain regions, particularly in the prefrontal cortex, while hippocampal activity was increased. This higher hippocampal activation was in turn associated with the participants' body mass index (BMI) and extinction errors. Our results demonstrate potentially dose-related enhancing effects of memantine and highlight involvement of hippocampal NMDAR in context-related extinction learning.